Improving EFL Learners Language Written Production Using Subtitled Videos - lasim muzammil (JURNAL ILMIAH BAHASA DAN SASTRA, 2014)
English as a Foreign Language (EFL) Learners tend to produce their speech or written production as they are associated with what they see and what they hear. So, they are able and desired to give comment spontaneously after watching and listening to them. Producing written language can, as a matter of fact, be detected from learners’ fluency, accuracy and complexity. This article endeavors to elaborate written language production done by university students by using English subtitled videos. Two intact groups were assigned to accomplish two different tasks; that is, one group watched the video with subtitle and the other one without subtitle. The result of the study reveals that learners who carry out the tasks of watching video with subtitle improve their ability in written production in terms of fluency and accuracy regardless to complexity.